A Forgotten Detail in the Cultural Landscape: a Ukrainian Version of Russian Formalism? National Identity, Avant-garde and Ideology in Literary Discussions in Soviet Ukraine (1920s–1930s) - Babak, Galina (Respectus Philologicus, 2017)
The 1920s in the Soviet Ukraine are characterised by significant variability of views on the meaning, social significance and mechanism of art and literature, however, all this theoretical and practical variety was limited by political restriction imposed by official communist ideology. Avant-garde groups and movements enriched modernist discussions by drawing attention to the fact that the revolution in arts and literature was of the same nature as political and social revolution. Numerous Soviet writers, poets, artists, philologists, etc. (including Ukrainian writers with their own national agenda) took part in these discussions; many of them were members of different literary movements, groups and organisations – and of course they had a different aesthetic orientation. One of the most important topics of Soviet theoretical discussions in the 1920s was the dualism of “form” and “content” in literature and art. Such discussions were held in Soviet Ukraine as well. Even though we cannot speak about “Ukrainian formalism” as an organised and disciplined aesthetic school, it is important to determine the “Ukrainian version” of correlation between universalist ideas of Russian formalism, internationalist Soviet ideology (in relation to the culture), and forming Ukrainian cultural identity.